Environmental Context and Site Selection of the Wuwangdun Tomb: A Brief Study on Chu Culture - Lu, Beini (Transactions on Environment, Energy and Earth Sciences, 2024)
The culture of the Chu Kingdom was once glory in Chinese history for a long duration, which was significantly different from the Central Plain Culture in Chinese Warring States Period. It has a high cultural value to study and conserve. The recent discovery of the Wuwangdun Tomb has provided new materials for studying the Chu Culture. Through the investigation of the site of this noble tomb, it has obvious evidences such as landscape features and funeral traditions to propose the importance of this noble tomb of the Chu State and its reflection of the evolution of this culture. The study of the essay decided to analysis the tomb’s environment and site selection, therefore finding its correlation part of the Chu Culture and its influence on later generations.